Ball‐on‐ring test validation for equibiaxial flexural strength testing of engineered ceramics. Issue 3 (25th March 2021) - Lupercio, Adrianna E.; Moshkelgosha, Ehsan; Winters, Riley C.; Doyle, Cayden; Mamivand, Mahmood; Nelson, Andrew T.; Jaques, Brian J.
Abstract: The validation of a ball‐on‐ring, equibiaxial flexural strength method to obtain the transverse rupture strength (TRS) of right cylindrical ceramic specimens was performed in this study. Validation of the test method was achieved using commercially available engineered high purity alumina disks and finite element (FE) model analysis. The validated fixture was then used to obtain the TRS and Weibull statistical analysis of MgO‐partially stabilized zirconia (MSZ) and Y2 O3 ‐partially stabilized zirconia (YSZ) ceramic disks. TRS data for alumina, MSZ, and YSZ agreed with the TRS values reported in the literature. A statistically relevant number of samples (N > 30) for each material were tested to allow for a Weibull statistical analysis. Weibull parameters for these materials were within the expected values for engineered ceramics. The characteristic strength for alumina, MSZ, and YSZ were determined to be 289, 786, and 814 MPa, respectively. The Weibull modulus was determined between 10 and 25 for each material, which is typical of engineered ceramics. In addition, FE model results were in close agreement with experimental fracture values for the three ceramic materials tested in this study. Abstract : This study combines synthesis with minimal flaws and testing of large sample sets for a valid statistical description of mechanical behavior with finite element modeling for ball‐on‐ring test fixture for obtaining the transverse rupture strength and Weibull parameters of engineered ceramics